PERANCANGAN APLIKASI MEDIA PEMBELAJARAN PENGENALAN TOKOH WAYANG KULIT BERBASIS ANDROID - Saraswati, Fauzia Puspa; Palekahelu, Dharmaputra T.; Tanone, Radius (Proceedings of KNASTIK, 2013)
The learning process of wayang or puppet that is still manual, minimizing students’ interest in knowing the characters of wayang. Wayang itself is a national heritage of culture that should be preserved. Also, wayang is an honored culture because it can be used to instill philosophical values that are able to shape someone’s characteristic. In this research, an application of learning media of introduction to wayang’s characters in an Android based mobile device which is interesting and interactive is made. This application is made by using the Actionscript programming language and is developed according to the developing procedure of interactive multimedia program for learning. The process and stage is started by the analysis of curriculum, and then the making of flow chart and storyboard, followed by collecting the materials, and finally the finishing process. This application consists of the materials about the characters of wayang and quiz about the materials given, so that it will increase students’ understanding. By the existence of the application, students’ interest in learning the characters of wayang is increasing, which can be proved by students’ marks that have got to the passing grade.